2014
DOI: 10.3390/min4020279
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Microbiological Approaches for Securing Mine Wastes and for Recovering Metals from Mine Waters

Abstract: Abstract:Mining of metals and coals generates solid and liquid wastes that are potentially hazardous to the environment. Traditional methods to reduce the production of pollutants from mining and to treat impacted water courses are mostly physico-chemical in nature, though passive remediation of mine waters utilizes reactions that are catalysed by microorganisms. This paper reviews recent advances in biotechnologies that have been proposed both to secure reactive mine tailings and to remediate mine waters. Emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 45 publications
(56 reference statements)
0
37
0
Order By: Relevance
“…Not surprisingly, most applications were applied to sulfidic materials that may generate acid over long periods. Some recent microbiological approaches to securing mine wastes and recovering metals from mine waters are highlighted in a review published in this journal ( [406] and references therein). The review covers a number of chemical methods for remediation of mine water, some of which have been commercialised but relevant to this review are the bioprocesses, including:…”
Section: Towards Responsible Waste Managementmentioning
confidence: 99%
“…Not surprisingly, most applications were applied to sulfidic materials that may generate acid over long periods. Some recent microbiological approaches to securing mine wastes and recovering metals from mine waters are highlighted in a review published in this journal ( [406] and references therein). The review covers a number of chemical methods for remediation of mine water, some of which have been commercialised but relevant to this review are the bioprocesses, including:…”
Section: Towards Responsible Waste Managementmentioning
confidence: 99%
“…Early research by Silverman and Ehrlich [22] hypothesised that microorganisms found in AMD environments may in fact be substantially responsible for its generation, with this phenomenon now well established [23]. For example, the activity of iron-and sulfur-oxidising microbes can accelerate the oxidation of pyrite and the subsequent acid generation rate by up to six orders of magnitude [24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the activity of iron-and sulfur-oxidising microbes can accelerate the oxidation of pyrite and the subsequent acid generation rate by up to six orders of magnitude [24]. While some chemoautotrophic microbes can exacerbate AMD, other groups of microorganisms, such as heterotrophic bacteria, can form protective biofilms on pyrite surfaces reducing the rate of AMD generation by reducing oxidant (O 2 , ferric iron) availability at the mineral surface and O 2 availability generally within the waters contained in the wastes [23,25]. Accordingly, microbe-mineral interactions are of considerable potential importance for effective and sustainable AMD management; however, such interactions are yet to be fully understood and exploited for AMD control.…”
Section: Introductionmentioning
confidence: 99%
“…The use of thermal desorption to volatilize Hg from Hg-contaminated soil and mine wastes is described by Navarro et al [15], and Mäkitalo et al [16] outline the properties of green liquor dregs (GLD), alkaline residual materials produced by sulfate paper mills. Johnson [17] reviews recent advances in biotechnologies using microorganisms that can reduce the reactivity of potentially hazardous mine tailings and selectively remove metals and other contaminants from mine waters.…”
mentioning
confidence: 99%